Gelatinous transformation of the bone marrow complicated by self induced starvation (Faculty of Medicine Universitas Indonesia, 2002)
Gelatinous bone marrow transformation (GMT) is rare. It has been found to be associated with severe illnesses and malnutrition (rarely). AÂ case report highlighting GMT as